IMPACT OF ECONOMIC CRISES ON FIRMS: A LITERATURE REVIEW - Isabirye, Joel (Annals of Spiru Haret University. Economic Series, 2021)
This paper examines literature that analyzes how economic crises affect firms. Eighty-five studies were examined with the overall aim of finding out the impact of crises on firms. Studies published between 1805 and 2018 were sampled purposively through digital database searches, to establish the most recent literature on the impact of crises on firms. Consequently, the majority of the work assessed focuses on the global economic crisis of 2007 and its effect on firms in a different country and regional contexts. The literature demonstrates that economic crises affect firms negatively and positively with a tendency for crises to affect firms more negatively. Negative impacts include a decline in demand, fall in profitability, debt problems, operational challenges, bankruptcy, loss of goodwill or public image, uncertainty, and scale down of operations. Positive impacts comprise stimulation of efficiency, and improved performance for strategic firms The review further establishes that the impact of crises on firms varies from firm to firm, which requires that to examine the impacts of economic crises on firms requires that the firms are studied on a case-to-case basis.